The Influence of the RADEC Learning Model Based on the TPACK Approach on the Improvement of Cultural Literacy for SMP/MTs Students - Wulandari, Wina; Muliatik, Sri; Arianto, Arianto (LP. Ma'arif Janggan Magetan, 2025)
This study aims to analyze the influence of the RADEC (Read, Answer, Discuss, Explain, and Create) learning model based on the TPACK (Technological Pedagogical Content Knowledge) framework on improving students' cultural literacy. This study used a quasi-experimental design with a pretest-posttest control group design model. The research subjects consisted of 65 students, 33 students each from SMP Negeri 23 Medan and 32 students from MTs Miftahussalam Medan. The experimental group was taught using the TPACK integrated RADEC model, while the control group used conventional lecture-based methods. Data was obtained through a cultural literacy test in the form of writing expository texts about local cultural values. Data analysis was carried out using SPSS 27 through normality tests, homogeneity tests, and independent sample t-tests. The results showed a significant increase in the cultural literacy ability of the experimental group compared to the control group. At SMP Negeri 23 Medan, the experimental group obtained an average posttest score of 87.12 compared to 61.36 in the control group. Meanwhile, at MTs Miftahussalam Medan, the average posttest of the experimental group reached 84.38 compared to 61.25 in the control group. These findings prove that the application of the TPACK-based RADEC model is effective in increasing student engagement and deepening their understanding of local culture through expository writing. The results of this study have practical implications for educators in designing technology-based learning that is contextual with local culture to strengthen the competencies of 21st century students.